If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + -5m + -6 = 0 Reorder the terms: -6 + 7m + -5m = 0 Combine like terms: 7m + -5m = 2m -6 + 2m = 0 Solving -6 + 2m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2m = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2m = 0 + 6 2m = 0 + 6 Combine like terms: 0 + 6 = 6 2m = 6 Divide each side by '2'. m = 3 Simplifying m = 3
| 7y-15x=9 | | 12p=7p+35 | | .25x+12=-.25x | | 6x-15=3x+12 | | 5y^4-7y^2+1.5=0 | | 7(x+1)-1=34 | | n-29-16=246 | | 6q+3-4q=9 | | t+(-3)=8 | | 9x-6y=8 | | t+3-3=8-3 | | a+8=12 | | .20x=7-.80x | | 3x+5=2x+9 | | 0.75+2(x-0.5)=3x-0.4 | | 16=.5x-8 | | -215+e+(-43)=-145 | | 34+p+112=78-7 | | -2(3u+x)+5(3x+u)= | | 17+38= | | 215+e+(-43)=-145 | | 3y+7=14 | | 5w+4z=-.7 | | 8-3(p-4)=2 | | -45=x+(-3)+50 | | -4r-2=6 | | 3x=3(x+4) | | -7m=9(m+4) | | 0.5(6-z)=z | | 7+8x-39=6x+32-10x | | 3(1-3r)+3=-3(4r-4) | | 2y+12=4x |